International political alignment during the Trump presidency: Voting at the UN general assembly - Martin Mosler; Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
We examine voting behavior of Western allied countries in line with the United States over the period 1949 until 2019. Descriptive statistics show that voting in line with the United States on resolutions in the United Nations General Assembly (UNGA) was on average 7.2 percentage points lower under Donald Trump than under the preceding United States presidents. The policy shift is especially pronounced for resolutions dealing with the Middle East. The decline in common UNGA voting behavior is significant for the resolution agreement rate and the absolute difference of ideal points. The results suggest that the alienation of Western allies is not driven by ideological distance based on a classical leftwing-rightwing government ideology scale.
Keywords: F51; F53; D72; D78; C23; 330; Donald Trump; voting alignment; UNGA; political alliances